Trends and outcomes of different mechanical circulatory support modalities for refractory cardiogenic shock in Takotsubo cardiomyopathy - Shafaqat Ali; Manoj Kumar; Yehya Khlidj; Faryal Farooq; Thannon Alsaeed; Muhammad Sultan; Pramod Kumar Ponna; Laxman Byreddi; Pratik Agrawal; Vijaywant Brar; Tarek Helmy; Taher Tayeb (American Heart Journal Plus)
Background: The use of mechanical circulatory support (MCS) devices in cardiogenic shock is growing. We aim to study trends and compare different MCS modalities in this population. Methods: The National Readmission Database (2016-2020) was queried to identify TTC-CS requiring MCS. Cohorts were stratified as ECMO (extracorporeal membrane oxygenation) compared to other short-term percutaneous left ventricular assist devices (Impella). The propensity score matching (PSM) was used to remove confounders. Pearson’s x2 test was applied to PSM-matched cohorts to compare outcomes. Additionally, we used multivariate regression and reported predictive margins for adjusted trend analysis. Results: Among 2,025 TTC-CS hospitalizations requiring MCS, 1,790 required Impella vs. 235 on ECMO. ECMO was more common in metropolitan teaching hospitals (72.2 % vs 56.1 %, p < 0.05). On PSM cohorts (N = 131), ECMO had higher in-hospital mortality (38.9 % vs. 20.6 %, p < 0.001), major bleeding (15.3 % vs. 2.3 %, p < 0.001), acute blood loss anemia (48.9 % vs. 19.1 %, p < 0.001) among others. Our subgroup analysis comparing ECMO when Left ventricular (LV) unloading was provided by either IABP or Impella, and Impella alone showed no difference in the short-term mortality (42.2 % vs. 33.3 %, p: 0.384). However, the rates of major bleeding (17.8 % vs. 0.0 %, p: 0.003) and acute blood loss anemia (55.6 % vs. 22.2 %, p: 0.001) were higher for ECMO cohort. Conclusion: In the absence of LV unloading, the ECMO utilization in TTC-CS had higher mortality and adverse events than Impella. The mortality difference was nonsignificant when concomitant LV unloading was provided with Impella or IABP in these patients.